CONTRIBUTIONS OF THE NEURODIVERSITY PARADIGM TO THE LEARNING AND INCLUSION OF NEURODIVERGENT STUDENTS - Gonçalves, Rosiane Ferreira; dos Santos, Elayne de Nazaré Almeida; Lima, Ana Paula Barros; Dourado, Natália de Fátima Silva; da Cruz, Walderney Pinheiro; Barbosa, Carlos Adriano Leite; Pinto, Yasmini Tuany Abdon (Seven Editora, 2025)
This article deals with the neurodiversity paradigm and its contributions to promoting inclusive education in Brazil, and seeks to analyze how this perspective has contributed to the inclusion of neurodivergent students in educational environments. A bibliographic analysis was carried out to understand the origin of the term neurodiversity and the theoretical basis of the neurodiversity paradigm, as well as its influences in the field of education. The analysis showed that the neurodiversity paradigm offers a holistic and inclusive approach to the learning and inclusion of neurodivergent students. By recognizing and valuing this diversity, schools can create more inclusive educational environments where all students have the opportunity to develop their potential. DOI: https://doi.org/10.56238/sevened2025.038-070